2011
DOI: 10.1111/j.1442-2018.2011.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health‐related quality of life by using a health promotion model among Iranian adolescent girls: A structural equation modeling approach

Abstract: Predicting the significant determinants of health-related quality of life through the application of structural equation modeling in adolescents has received little attention in the health education and health promotion literature. The purpose of this study was to investigate the relationships between self-efficacy, barriers, social support, health-promoting lifestyle, and health-related quality of life among Iranian adolescent girls. Pender's health promotion model guided this study. This was a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 26 publications
5
32
0
1
Order By: Relevance
“…Lifestyle-related factors were assessed by the HPLP-II, which has been widely used as a measuring tool for assessing health-promoting behavior [35], and has been considered reliable and valid both domestically and internationally [36,37]. The HPLP-II is comprised of 52 items that assess six behavioral dimensions of lifestyle: spiritual growth, health responsibility, sports and exercise, nutrition, interpersonal relationships and stress management.…”
Section: Methodsmentioning
confidence: 99%
“…Lifestyle-related factors were assessed by the HPLP-II, which has been widely used as a measuring tool for assessing health-promoting behavior [35], and has been considered reliable and valid both domestically and internationally [36,37]. The HPLP-II is comprised of 52 items that assess six behavioral dimensions of lifestyle: spiritual growth, health responsibility, sports and exercise, nutrition, interpersonal relationships and stress management.…”
Section: Methodsmentioning
confidence: 99%
“…Each dimension was scored from 0 through 100. The SF-36 has been validated by Montazeri, Goshtasebi, Vahdaninia, and Gandek (2005) as having a Cronbach’s alpha coefficient of .95 for the Iranian population (Mohamadian et al, 2011; Montazeri et al, 2005). The CPSC questionnaire had 54 items, and each item had two options (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to presume that overweight is a barrier to the initiation of physical activity. Perceived barriers to action are shown to correlate with a lower level of self-efficacy, which in turn demonstrates a direct effect on health-promoting behavior and an indirect effect on the quality of life (Mohamadian et al, 2011). The close link between BMI and exercise self-efficacy was demonstrated by an intervention study of an exercise and nutrition program, which found that changes in self-efficacy for physical activity and controlled eating accounted for 26% of the total variance explained in the BMI change (Annesi & Gorjala, 2010).…”
Section: Mean (Sd)mentioning
confidence: 97%
“…One of the hypotheses argues that self-efficacy promotes change and long-term adherence to a number of health-related behaviors including exercise (Conraads et al, 2012;Tierney et al, 2012), diet (Ferranti et al, 2014;Sharp & Salyer, 2012), treatment compliance (Chair et al, 2013;McAuley et al, 2011), self-care behavior (Bohanny et al, 2013), and general health-promoting behavior (Lo, Chair, & Lee, 2015). A study in Iran explained the quality of life in 500 participants by using structural equation modeling approach (Mohamadian et al, 2011). The results showed that health-promoting behavior resulting from enhanced self-efficacy and other factors significantly influenced the quality of life.…”
Section: Introductionmentioning
confidence: 99%